Inventions, public subsidies and market launch: Opportunities and limits of patenting support in Argentina; Invenciones, subsidios públicos y llegada al mercado: oportunidades y límites del apoyo al patentamiento en Argentina - Darío Milesi; Carlos Aggio; Vladimiro Verre (Estudios de Economía, 2024)
ANR Patentes is an Argentinean program that gives grants for patents applications to innovative firms, entrepreneurs and researchers. Throughout the period 2007-2017, 83 projects (out of 195) were funded. Based on secondary sources and a survey conducted to beneficiaries, this study reconstructs the progress made by the patent applicants. The results show, on the one hand, that a high percentage of the patents have been granted, and, on the other hand, a group of projects are facing difficulties to reach the market. Thus, the study suggests the necessity to complement ANR Patentes with other instruments oriented to foster entrepreneurship and productive development.
Keywords: O30; O32; O34; 330; Public subsidy; patent; market